Brief Report From the 4th International Meeting on Bone Marrow Adiposity (BMA2018) - Penel, Guillaume; Kerckhofs, Greet; Chauveau, Christophe (Frontiers in Endocrinology, 2019)
The 4th International Meeting on Bone Marrow Adiposity (BMA2018) was hosted at the premises of the Regional Government of Hauts de France in Lille, from August 29th to August 31st 2018. This congress brought together physicians and scientists working on rheumatology and bone biology, oncology, hematology, endocrinology, and metabolic diseases, all interested in bone marrow adiposity. They shared their opinions, hypothesis, and original results. Six invited keynotes were given by S. Badr, B.C.J. van der Eerden, M.J. Moreno Aliaga, O. Naveiras, C.J. Rosen, and A.V. Schwartz. Twenty-one short talks were also given. This report briefly summarizes the scientific content of the meeting and the progress of the working groups of the BMA Society (http://bma-society.org/).